1999
DOI: 10.1143/jjap.38.7194
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Tests of Ni–P Amorphous Alloy Microcantilever Beams

Abstract: Fatigue life and fatigue crack propagation tests have been performed on microsized Ni-P amorphous alloy specimens to investigate the fatigue properties of this material. The material used was a Ni-11.5 wt%P amorphous thin film. The specimens tested were cantilever-beam-type specimen with dimensions of 30 × 12 × 50 µm 3 prepared by focused ion beam machining. Notches with a depth of 3 µm were introduced in some specimens. The entire set of fatigue tests was performed using a newly developed fatigue testing mach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 5 publications
(5 reference statements)
0
6
0
Order By: Relevance
“…Some examples are listed in the following: uniaxial cyclic loading tests were performed on single crystal specimens and a reduction in fatigue life was observed for specific strain levels [8]. The fracture caused by fatigue loading on Ni-P amorphous alloy microcantilevers was studied and the fatigue strength resulted about one-third of the static bending strength [9]. From the aspect of fracture striations the authors concluded that the crack propagation occurs by cyclic plastic deformation at the crack tip.…”
Section: "In-situ" Configurationmentioning
confidence: 99%
“…Some examples are listed in the following: uniaxial cyclic loading tests were performed on single crystal specimens and a reduction in fatigue life was observed for specific strain levels [8]. The fracture caused by fatigue loading on Ni-P amorphous alloy microcantilevers was studied and the fatigue strength resulted about one-third of the static bending strength [9]. From the aspect of fracture striations the authors concluded that the crack propagation occurs by cyclic plastic deformation at the crack tip.…”
Section: "In-situ" Configurationmentioning
confidence: 99%
“…In the case of actual use of amorphous metals for mechanical components, their mechanical properties should be evaluated as fundamental design data. Thus, the mechanical properties of amorphous metals have been investigated by many researchers in recent years [7][8][9]. However, the most important property for the actual machine design is fatigue strength of the structural materials, since every product should endure during a definite period without failure under cyclic loadings.…”
Section: Introductionmentioning
confidence: 99%
“…Although there have been extensive studies on the mechanical behavior of microwire materials in the past two decades, such as static tensile test [ 24 27 ], micro/nanoindentation measurement [ 28 30 ], bending measurement [ 31 33 ], and dynamic resonance frequency fatigue test [ 34 , 35 ], little was reported on the behavior of microwire under the torsional loading [ 36 38 ]. Torsion of thin wires is a fundamental and excellent approach to explore the mechanical behavior, from elastic deformation, through yielding, to the strain-hardening regime.…”
Section: Introductionmentioning
confidence: 99%